DETECTION OF CRYPTOSPORIDIUM IN IMMUNOSUPPRESSED PATIENTS - Baqai, R.; Anwar, S.; Kazmi, S. U. (Journal of Ayub Medical College Abbottabad, 2005)
Background: Cryptosporidium is an important cause of diarrhoeal disease in children and immunosuppressed persons. It is an opportunistic pathogen. A study was done to determine the frequency of Cryptosporidium in immunosuppressed persons. Methods: Fecal samples were collected from Jinnah Postgraduate Medical Centre Karachi during July to December 2003 and they consisted of three categories of patients which included cancer patients (10) diabetics (20) and patients on dialysis (20). Direct microscopy in saline and iodine was done to detect parasites. Detection of Cryptosporidium from fecal samples was done by Kinyoun method. Bacteriological study was also done to determine any bacterial pathogens. Results: Out of 50 fecal samples Cryptosporidium was found in 20 (40%) of cases. Among the different groups Cryptosporidium was found in 80% of cancer patients, 25% diabetics and 35% dialysis patients. Distribution of Cryptosporidium according to gender indicated more cases in males (87%) among cancer patients and 40% among dialyzed patients while diabetic patients showed similar distribution. Among the different age groups male patients were found to be between 40-49 years group for all categories of patients while more positive cases were detected in females in 30-39 years age group. Direct microscopy did not indicate any ova or parasite and bacteriological study indicated Salmonella and Shigella spp. in stool samples. Conclusion: This study provides indication of the possibility of Cryptosporodisis in immunosuppressed patient and further comprehensive study is required to clearly establish the relationship of opportunistic infections in immunosuppressed patients. Keywords: Immunosuppressed patients, Cryptosporidium, Cryptosporodosis